Effect of replacing maize by Kangni (Setaria italica) on body measurement and carcass traits of broilers - Shekhawat, Ranveer Singh; Kumar, Upendra (Annals of Agricultural Research, 2018)
An experiment was conducted for 8 weeks, utilizing 250 day-old broiler chicks, randomly divided in five groups of 50 chicks each, to study the effect of replacing maize quantitatively at 0, 25, 50, 75 and 100 per cent level with Kangni (Setaria italica) in isocaloric and isonitrogenous ration. The keel length and shank length in broilers fed kangni diets were marginally longer than fed maize diet but the difference did not reach to the level of statistical significance. Carcass traits (dressed weight, eviscerated weight) were not affected by replacement of maize with kangni. The mortality during entire experimental period was 4.4 per cent in all the dietary groups the maximum mortality (10%) was observed in 100 per cent kangni fed group, while no mortality was observed in 50 per cent kangni based ratio fed group. Replacement of maize by kangni margenly increase the keel length, shank length, dressed weight and eviscerated weight.